PENYELESAIAN SENGKETA WAKAF TANAH DI KECAMATAN BAYANG OLEH PENGADILAN AGAMA KELAS II PAINAN KABUPATEN PESISIR SELATAN - Yose Leonando (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2019)
The issue of land ownership has become a fundamental problem in Indonesia. One of the conflicts is a dispute of waqf land, both property and customary rights. The lack of assertiveness of the waqf rules on the natural land right in West Sumatera also triggered conflict, because the natural right is not accommodated as an object of land registration, so the deed of customary land does not guarantee legal certainty in accordance with the waqf rule in Indonesia. The dispute of Waqaf land in the district of Bayang appear because of many aspects such as customary land as the object of Waqaf, the economic value of the property, the increasing of the population, the need of land, Wakif giving all the customary land as Waqaf, Nazhir’s ineffective land use, the land given without the knowledge of the members of community, the regulation of Waqaf land not accommodated well in law number 41 of 2004. The method used is descriptive, which describes the facts and the real condition of land waqf of property right and customary right in the district of Bayang, with an analysis of a normative legal approach. This study uses an empirical juridical approach by researching with emphasis on the application of the waqf legal in the form of law. The collected data are in the way of primary data obtained from related parties in Waqaf land in the research location, secondary data obtained from secondary, primary, and linear legal materials. From the research it customary land waqf is the leading cause of waqf disputes in the district of Bayang, because many waqf lands are given with unwritten document (verbally) and not registered. The solution to waqf land disputes in Bayang District uses non-ligitation and ligitation settlement efforts. The conflict of waqf of customary land was solved by a non-ligitation manner, through mediation of the adat institution, Gurun Panjang KAN, while the dispute over property rights at the village of Taratak Teleng Puluik Puluik was complete by ligitation in Painan Religious Court.